A 2.75 V ammonium‐based dual‐ion battery. (17th November 2022) - Zhao, Zhiming; Lei, Yongjiu; Shi, Lin; Tian, Zhengnan; Hedhili, Mohamed N.; Khan, Yusuf; Alshareef, Husam N.
Abstract: The popular metal‐ion batteries (MIBs) suffer from environmental and economic issues because of their heavy dependency on nonrenewable metals. Here, we propose a metal‐free ammonium (NH4 + )‐based dual‐ion battery with a record‐breaking operation voltage of 2.75 V. The working mechanism of this sustainable battery involves the reversible anion (PF6 − ) intercalation chemistry in graphite cathode and NH4 + intercalation behavior in PTCDI (3, 4, 9, 10‐perylenetetracarboxylic diimide) anode. This new battery configuration successfully circumvented the reduction susceptibility of NH4 + and the lack of mature NH4 + ‐rich cathodes for NH4 + ion batteries (AIBs). The customized organic NH4 + electrolyte endows the graphite||PTCDI full battery with durable longevity (over 1000 cycles) and a high energy density (200 Wh kg −1 ). We show that the development of AIBs should be high‐voltage‐oriented while circumventing low operation potential to avoid NH4 + reduction. Abstract : We bypassed the reduction susceptibility of NH4 + and promoted the NH4 + ion battery toward a record‐breaking operation voltage of 2.75 V by co‐utilizing the storage of the other significant charge carrier in electrolytes, viz, anions, realizing a high‐voltage metal‐free battery.